Unveiling a Three Phase Mixed Heterojunction via Phase‐Selective Anchoring of Polymer for Efficient Photocatalysis. Issue 15 (25th February 2022) - Jadhav, Amol R; Bui, Viet Q.; Cho, Yunhee; Liu, Yang; Kumar, Ashwani; Kim, Hyojung; Ajmal, Sara; Liu, Xinghui; Saqlain, Shahid; Lee, Jinsun; Kim, Hyunjung; Kim, Young Dok; et al.
Abstract: The ligand‐to‐metal charge transfer (LMCT) facilitated activation of TiO2 has noteworthy potential for solar energy harvesting. However, the fast back electron transfer from TiO2 to an oxidized sensitizer is a key limiting factor causing low photocatalyst efficiency. Herein, a new catalyst design to both increase LMCT efficiency and minimize the back electron transfer is presented. A phase‐selective modification of mixed‐phase TiO2 (anatase: rutile interface) with poly‐salophen organic polymer is developed. The salophen and salen family organic monomers are selectively bound and polymerized on the anatase phase but not the rutile phase, which results in the formation of a three‐phase system. Such a three‐phase system converts an unfavorable polymer TiO2 core‐shell structure to an intimately mixed blend morphology, consisting of interfaced crystalline rutile TiO2 and an amorphous polymer‐covered anatase‐phase TiO2 . The developed mixed‐blend morphology poly‐S@P25 can produce H2 of 37 410 µmol h –1 g –1 of polymer, which is ≈3.4 times higher than core‐shell poly‐S@anatase TiO2 . This approach overcomes the drawback of the traditional core‐shell structured system for efficient electron harvesting from the LMCT process. Abstract : This work demonstrates a platform for designing an organic polymer: inorganic metal oxide semiconductor heterojunction photocatalyst to promote solar light‐driven hydrogen production from water. The newly designed poly‐salophen@A‐TiO2 /R‐TiO2 three‐phase system heterojunction effectively improves the charge transfer rate from polymer to TiO2 and simultaneously suppresses the back electron transfer rate, resulting in efficient and stable H2 production under solar light.